History of Colegio Pedro II equating to the status of Federal Institute: Legislation and current structure (Research, Society and Development, 2021)
This article is based on the 12-year period between 2008 (the year in which the Federal Network was created) and 2020. Colégio Pedro II was founded in 1837, and its activities range from early childhood education to Stricto Senso graduate school. Law No. 11,892 of 2008 created the Federal Institute, and its wording was updated by Law No. 12,677 of 2012, to include Colégio Pedro II in the Federal Network of Scientific, Professional and Technological Education. Law    12.677/12 retained the traditional name “Colégio Pedro II”, however, equating it to the condition of Federal Institute of Education, Science and Technology. This article focuses on the legal aspects of this assimilation, explaining legal concepts and commenting on the main provisions of the relevant legislation. In addition to integrating the Brazilian legal system, the legislation also contributed to the development of Colégio Pedro II and professional education in Brazil.